Three species of Termitomyces (Lyophyllaceae, Agaricales) from Punjab, India - KAUR, HARWINDER (Mushroom Research, 2022)
Three Termitomyces samples were collected in fungal surveys during 2008–2012 at different localities and sub-localities of district Ludhiana, Punjab. Detailed morphological examination showed the one of these collections represent a new species and remaining two species are new to district Ludhiana, Punjab. The macroscopic and microscopic characters with camera lucida establish the new species which we describe and illustrate in this paper. The new species, Termitomyces punjabensis sp. nov. has been taxonomically described and illustrated for the first time from India and reported as new to science.       Key words: India, Termitomyces, Lyophyllaceae, taxonomy.